Emotional Intelligence Scale for International Students: A Proposal for a Developed Version - AL-Qadri, Abdo Hasan; Zhao, Wei; Li, Miao; Al-khresheh, Mohammad; Boudouaia, Azzeddine (Frontiers in Education, 2022)
In higher education, making international students aware of their EI could improve emotional awareness, adaptability, and functioning, thereby assisting in day-to-day interactions and adapting to life in a foreign country. Incorporating an Emotional Intelligence Scale (EIS) could aid in the on boarding of international students. This study aimed to develop and validate an EIS capable of accurately measuring EI amongst international students attending a teaching university in Northwest China. The sample consisted of 482 male and female undergraduate and graduate students ranging in age from 18 to 40. The multivariate statistical technique was used for data reduction or factor analysis. Exploratory and confirmatory factor analyses showed that the 24-item distributed among the four-factor model was a good fit based on the modification indices. The four factors considered were Understanding and Regulation, Positive Affect, Optimism, and Utilization. Techniques employed to assess the reliability of the EIS included Cronbach’s alpha coefficient, test/re-test stability, Composite Reliability (CR), and Average Variance Extracted (AVE). Of interest, there were no statistically significant differences between post-graduate/graduate students or different genders. Findings indicated that the EIS might effectively be employed to measure EI in this target population.